(untitled) (Research, Society and Development, 2021)
This article has as its objective a comparative study of the electrochemical treatment of slurry generated in landfills carried out with Dimensionally Stable Anodes (DSA) (Ti/Ru0.3Ti0.7O2) and Boron Doped Diamond (BDD). From the capacity planning and control (PCC), the central composite rotated design (DCCR) was obtained, whose independent variables in the electrolysis process were current density, time and electrolyte concentration. The removal of Total Organic Carbon (dependent variable) was 15.40% with current density 158 mA cm-², electrolysis time 15 minutes and 0.2 mol L-1 of the NaCl electrolyte using DSA. With the BDD, at the optimum point at 82 mA cm-², 18.5 minutes and 0.19 mol L-1, 77% removal of the organic load and discoloration of approximately 40% Ultraviolet-Visible.